Development and Evaluation of Fenofibrate Surface Solid Dispersion for Improved Solubility and Dissolution Rate - Hosmani, Avinash Hanmant; Patil, Nikhil Dilip; Pawar, Arti Achut; Honmane, Sandip Mohan; Thorat, Yogesh Shripad (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: The current work aimed to prepare and characterize Surface-Solid Dispersion (SSD) of Fenofibrate (FNB) in order to improve its solubility and dissolution. Materials and Methods: SSD of FNB has been prepared using solvent evaporation techniques through the combination of hydrophilic polymers such as Aerosil 200, Avicel PH 101, Sodium Starch Glycolate (SSG), Crospovidone (CP) and Croscarmellose Sodium (CCS). The produced SSDs were tested for saturation solubility, production yield, Fourier-Transform Infrared Spectroscopy (FTIR), Powder X-ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), and in vitro dissolution study. Results: PXRD results demonstrated a conversion of the crystalline FNB to an amorphous state when formulated with the carrier, which improved FNB solubility. A decrease in the endothermic peak with respect to FNB in the DSC thermogram of SSD, confirms the loss of crystallinity. Hydrophilic carriers such as Aerosil 200 and CCS at 1:2 (drug: polymer) ratios were found to increase solubility by 3 fold. Conclusion: As a result, the creation of SSD using hydrophilic polymers (Aerosil 200 and CCS) by solvent evaporation seemed to be a novel method that enhanced FNB solubility and dissolution.
Keywords: FNB; Surface solid dispersion; Solvent evaporation; Solubility; Dissolution rate